Associação entre bullying, bruxismo noturno e satisfação de vida em adolescentes - Lívia Bonfim Fulgêncio (2013)
The aim of this study was to investigate the association between life satisfaction, bullying and sleep bruxism with sociodemographic aspects in adolescents. We conducted a cross-sectional study of 366 adolescents aged between 13 and 15 years enrolled in five city schools Itabira, Minas Gerais, Brazil. The adolescents completed self-report questionnaires on life satisfaction through the Multidimensional Scale of Life Satisfaction for Adolescents (MSLSA) and on the occurrence of bullying in school, compiled from questions drawn from the instrument used in the National Health Survey the School (NHSS). Parents answered questions related to the presence of sleep bruxism prepared in accordance with the criteria of the American Association of Sleep Medicine (AASM) and the question format of the Brazilian version of the PSQI-BR (Pittsburgh Sleep Questionnaire), and also respond to questionnaires the socioeconomic aspects from Brazil Economic Classification Criterion (BECC). Data analysis was performed using SPSS 21.0 and included frequency distribution, chi-square test, chi-square for linear trend and Fisher's exact, with a 5% significance level. The Cronbach's alpha test was conducted to check the reliability of the multidimensional scale of life satisfaction when applied to adolescents in the age group of this study. There were 163 boys (44.5%) and 203 girls (55.5%). The average age of adolescent research participants was 13.7 (SD = 0.702). Most participants belonged to class less favored (54.9%). The prevalence of sleep bruxism was 6.8% according to parents' reports. Episodes of bullying were reported by 8.2% of adolescents. Higher frequency of bruxism were observed among younger adolescents (p = 0.002) and from families more economically favored (p = 0.049). There was no statistically significant association between sleep bruxism, gender (p = 0.095) and bullying (p = 0.708). The highest values of life satisfaction in family size were observed among younger adolescents (p = 0.004) and from families more economically favored (p <0.001). Higher values of life satisfaction in school size were associated with younger adolescents (p <0.001). We observed a statistically significant association between sleep bruxism and high levels of satisfaction in the dimensions self-efficacy (p = 0.002) and self (p = 0.031) The self-efficacy scale had higher life satisfaction among younger adolescents (p = 0.001). High levels of satisfaction in the dimension nonviolence were significantly associated economic classes favored (p <0.001). We assessed life satisfaction and bullying, but not statistically significant association was found. It was concluded that the assessment of certain areas of life satisfaction and economic class are associated with the sleep bruxism in adolescents. Once the high evaluation of themselves (self field) and high satisfaction in fulfilling tasks (domain self-efficacy) represents individuals with a higher propensity to sleep bruxism, and that adolescent family more economically favored by executing larger amount of tasks and higher levels of demand, also have a greater tendency to sleep bruxism. Underprivileged class has a higher propensity to engage in fights and arguments, (situations of violence).